Efeitos das dimensões extras em sistemas atômicos e o problema do raio do próton - Lêmos, Adiel da Silva (2018)
Uniﬁcation theories that include gravitation, such as the Kaluza-Klein theory and string theory, predict the existence of the supplementary space. Motivated by large extra dimensions theory, we explicitly examined the inﬂuence of the postulates extradimensionality of spacetime on atomic systems where the usual four-dimensional gravitational effects are negligible. Initially, we present a complementary method to constrain the extra-dimensional models through the spectroscopy of hydrogen-like atoms. Assuming that the gravitational potential energy, modiﬁed by the existence of extra dimensions, can be treated as a small perturbation in comparison to the atomic Hamiltonian, we found empirical bounds on the radius of the extra dimensions – or, alternatively, on the higher-dimensional Planck mass – more stringent than those obtained through the Large Hadron Collider (LHC). Subsequently, we addressed the proton radius puzzle that deals with the incompatibility between the theoretical predictions derived fromQuantumElectrodynamics(QED)andexperimentalmeasurementsinvolvingtransitions in electronic and muonic hydrogen atoms. This puzzle presents itself as an energy excess in the measurement of the Lamb Shift in muonic hydrogen compared to the theoretical prediction calculated with the proton radius value recommended by CODATA. We show that this energy excess, in the thick brane scenario, can be explained by the gravitational interaction ampliﬁed by the extra dimensions. Thus, this would be the ﬁrst evidence of the supposed spatial extra dimensions.